Acceptability, Shelf Life and Nutritional Quality of Moringa-Supplemented Rice Crackers (2013)
Moringa oleifera Lam. or malunggay is a locally available crop with excellent nutritional and health qualities. The use of this vegetables as a dietary supplement to rice cracker was evaluated. Leaves were added in fresh and powdered forms at different levels: 1, 2 and 5%(wt/wt rice). Laboratory sensory evaluation showed that all samples were greenish and tasted grassy but those with up to 2% fresh moringa (MF) or powdered moringa (MP) were as crunchy and acceptables as the control. Consumer survey of Grade 6 pupils (11-12 yr, n=30) showed 100% acceptability of crackers with up to 2% MP, while adult consumers (18-54 yr, n=30) found the sample with 1% MF comparable with the control and favored it over the other treatments. The best treatments, 1% MF and 2% MP, had significantly higher beta-carotene, vitamin C, and calcium levels than the control. Water activity values of crackers with 1% MF and 2% MP remained below 0.6 up to 3wk and microbial counts were within acceptable limits. Sensory scores were comparable with those of the control even at the end of the storage test. These results show that malunggay can be used in the development of nutrient-enriched rice crackers with good storage quality ang high consumer acceptability.